On the European readiness for flexicurity: Empirical evidence with OECD/HBS methodologies and reform proposals - Andranik Tangian (Hans-Böckler-Stiftung, Wirtschafts- und Sozialwissenschaftliches Institut (WSI), 2008)
The Fourth European Working Conditions Survey (European Foundation 2007) is used to investigate the readiness of Europe to flexicurity labour market reforms proposed by the European Commission (= flexibilization of employment relations compensated by improvements in employment security backed up by lifelong learning). For this purpose, composite indicators of flexibility, precariousness and decentness of work are constructed with the OECD and HBS (Hans Boeckler Stiftung) methodologies which differ in scaling. Then the indices are visualized with specially designed tabular graphs and analysed. Both methodologies give quite similar results. It is revealed that (1) factual flexibility (as it is practiced) radically differs from institutional flexibility (prescribed by employment protection legislation), (2) flexibility and precariousness of work correlate with statistical certainty, moreover, no country combines high flexibility and low precariousness; (3) flexibilization has the strongest negative effect on employability; (4) there is an acute shortage of learning options, (5) learning makes a negative impact on job satisfaction, at the same time job stability is top esteemed, but not income which is ranked only 6th, and (6) working conditions of flexibly employed is worse than of normally employed, being even below the European average. It implies that the Commission's conception of flexicurity, neglecting the socio-economic reality, can be hardly efficient and successful. Therefore, an alternative implementation of flexicurity is proposed in the form of flexinsurance which assumes that the employer's contribution to social security should be proportional to the flexibility (precariousness) of the employment contract. To stimulate employers to equalize working conditions of normal and atypical employees, it is proposed to introduce a workplace tax for bad working conditions which should protect 'the working environment' in the same way as the green tax protects the natural environment.
Keywords: 330; Flexicurity; Arbeitsmarktflexibilisierung; Soziale Sicherung; Arbeitsbedingungen; Ungeschützte Beschäftigung; Arbeitsplatz; Steuer; EU-Staaten